Single-cell analysis reveals the continuum of human lympho-myeloid progenitor cells. (January 2018) - Karamitros, Dimitris; Stoilova, Bilyana; Aboukhalil, Zahra; Hamey, Fiona; Reinisch, Andreas; Samitsch, Marina; Quek, Lynn; Otto, Georg; Repapi, Emmanouela; Doondeea, Jessica; Usukhbayar, Batchimeg; Calvo, Julien; et al.
Abstract The hierarchy of human hemopoietic progenitor cells that produce lymphoid and granulocytic–monocytic (myeloid) lineages is unclear. Multiple progenitor populations produce lymphoid and myeloid cells, but they remain incompletely characterized. Here we demonstrated that lympho-myeloid progenitor populations in cord blood — lymphoid-primed multi-potential progenitors (LMPPs), granulocyte-macrophage progenitors (GMPs) and multi-lymphoid progenitors (MLPs) — were functionally and transcriptionally distinct and heterogeneous at the clonal level, with progenitors of many different functional potentials present. Although most progenitors had the potential to develop into only one mature cell type ('uni-lineage potential'), bi- and rarer multi-lineage progenitors were present among LMPPs, GMPs and MLPs. Those findings, coupled with single-cell expression analyses, suggest that a continuum of progenitors execute lymphoid and myeloid differentiation, rather than only uni-lineage progenitors' being present downstream of stem cells. Vyas and colleagues show that a continuum of hemopoietic progenitor cells from human cord blood execute lymphoid and myeloid differentiation.